2017
DOI: 10.1002/mds.26930
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in cerebellar and basal ganglia networks during a visuospatial task in cervical dystonia

Abstract: This promotes the view that dystonia results from miscommunication between the basal ganglia and cerebellar loops, thus providing new insights into the brain regions essential for the development of cervical dystonia. © 2017 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 73 publications
(92 reference statements)
12
50
1
Order By: Relevance
“…Nevertheless, it is an intriguing observation, as cerebellar lobule VI has been found to be involved not only in human sensorimotor integration and movement control in functional imaging but also direct cortical stimulation studies . Beyond that, atrophy of lobule VI, respectively, lobule VIIa has been reported in PD and early onset Huntington disease, whereas fMRI hypo‐metabolism in lobule VI has been reported in both dystonia and the parkinsonian variant of multiple system atrophy and in a motor timing trial in PD .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is an intriguing observation, as cerebellar lobule VI has been found to be involved not only in human sensorimotor integration and movement control in functional imaging but also direct cortical stimulation studies . Beyond that, atrophy of lobule VI, respectively, lobule VIIa has been reported in PD and early onset Huntington disease, whereas fMRI hypo‐metabolism in lobule VI has been reported in both dystonia and the parkinsonian variant of multiple system atrophy and in a motor timing trial in PD .…”
Section: Discussionmentioning
confidence: 99%
“…Many of the genetic diseases reviewed here encompass complex phenotypes due to neurodegeneration of multiple systems and structures, including the alteration of both basal ganglia and cerebellum, which may explain the occurrence of dystonia in the setting of ataxia and other neurological features. There is growing evidence of an important role of the cerebellar dysfunction in dystonia . Animal models of generalized dystonia showed abnormal cerebellar activity, and dystonia can be independent of the basal ganglia and can be alleviated or abolished by inactivation of the cerebellum .…”
Section: Methodsmentioning
confidence: 99%
“…2A). In addition, these studies revealed that gray matter changes in focal dystonias further extend to the other divisions of the basal ganglia, most commonly including caudate nucleus and globus pallidus, as well as thalamus and cerebellum (Delmaire et al, 2005; Draganski et al, 2003; Egger et al, 2007; Filip et al, 2017; Obermann et al, 2007; Pantano et al, 2011; Simonyan & Ludlow, 2012; Waugh et al, 2016; Zeuner et al, 2015). More importantly, structural alterations were shown to involve some of the key cortical regions, responsible for sensorimotor processing, integration and motor execution, such as frontoparietal, supplementary motor and primary sensorimotor areas (Delmaire et al, 2005; Draganski et al, 2003; Egger et al, 2007; Garraux et al, 2004; Granert, Peller, Jabusch, et al, 2011; Horovitz, Gallea, Najee-Ullah, & Hallett, 2013; Martino et al, 2011; Pantano et al, 2011; Ramdhani et al, 2014; Simonyan & Ludlow, 2012).…”
Section: Structural Neuroimaging Of Dystoniamentioning
confidence: 97%